Assessing the value of your technology - Tipping, James W.
James W. Tipping, Eugen Zeffren and Alan R. Fusfeld explain how the Technology Value Pyramid and its associated menu of metrics can be used to analyze the performance of an R&D organization and to establish its contribution to the overall business.
With its menu of 33 metrics, the Technology Value Pyramid provides a model of sustained innovation and accountability.
R&D's role in the innovation process can be meaningfully represented by a hierarchy of managerial factors (The Technology Value Pyramid) that provide the foundations, links to strategy and financial outcomes for the corporation. The recognition of these TVP factors, together with an assembled menu of metrics, allows the model to be used to track the contribution to innovation performance at different levels of the TVP. The TVP model can be used to track the performance both prospectively and retrospectively, to diagnose weaknesses in the R&D organization and to plan for improvement in R&D contribution to the corporation. The various R&D stakeholders have different interests and perspectives on the innovation process, and these are accommodated by the TVP model and the menu of metrics.
Keywords: Technology value